Laparoscopic Transplantation Following Transvaginal Insertion of the Kidney: Description of Technique and Outcome. Issue 7 (23rd March 2015) - Modi, P.; Pal, B.; Kumar, S.; Modi, J.; Saifee, Y.; Nagraj, R.; Qadri, J.; Sharmah, A.; Agrawal, R.; Modi, M.; Shah, V.; Kute, V.; et al.
<x xml:space="preserve">Abstract</x> Laparoscopic kidney transplantation (LKT) is well accepted modality of treatment for ESRD patients at our center. Usually, the kidney is inserted through small Pfannenstiel incision. With the permission of the Internal Review Board, we carried out LKT in eight female recipients following insertion of the kidney through the vagina. The kidney was procured by the retroperitoneoscopic approach. Antibiotic prophylaxis was given. All cases were carried out successfully with immediate graft function and 100% graft and patient survival at 1 year of follow‐up. Estimated glomerular filtration rate at 1 month and 1 year was similar to eight randomly selected female recipients who underwent open kidney transplantation (OKT). No analgesia was required in seven out of eight patients after the 3rd postoperative day. In summary, vaginal insertion of kidney and LKT is safe and feasible in a selected group of patients. It is associated with better analgesia and has similar allograft function as compare to OKT.